Comparative study on safety and efficacy of cervical ripening agents misoprostol and dinoprostone in the induction of labour - Shakya, Rajani; Shrestha, Joshna; Thapa, Panna (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aim: To compare the safety and efficacy of two commercially available prostaglandin analogues, misoprostol and dinoprostone as cervical ripening agents. Methods: Patients with a term, vertex, singleton pregnancy and a Bishop score of 4 or less were randomly assigned to receive misoprostol pessary (n = 35, 50 μg intravaginally, maximum dose of up to six pessary) or dinoprostone gel (n = 31, 0.5 mg intracervically; administered twice 6hrs apart). Patients were monitored throughout the period. If there was no progress in cervical dilatation or effective uterine contraction even after maximum dose of dinoprostone or misoprostol, patients were taken for cesarean section. Patients who were able to achieve Bishop’s score more than 7 but the delivery was not progressing, were augmented with intravenous oxytocin infusion. Result: Both drugs were found to be equally effective in improving Bishop’s score. There was significant reduction in the need for oxytocin augmentation in misoprostol (37.1%) group than in dinoprostone (67.7%) group. However, abnormal fetal heart rate was observed in 3 (8.6%) cases in misoprostol group and 2 (6.5%) in dinoprostone group. There was no statistically significant difference in meconium passage in two groups. But there were no significant differences in the mean induction to delivery time in dinoprostone and misoprostol group. Cesarean sections in dinoprostone and misoprostol groups were 32.3% and 28.6% respectively. No uterine hyperstimulation was observed, Apgar score less than 7 at 1 minute was 6 (19.4%) and 11 (31.4%) neonates in dinoprostone and misoprostol group and Apgar score less than 7 at 5 minutes was found only in one neonate of dinoprostone group. Conclusion: Vaginal misoprostol is an effective, safer and cheaper alternative to dinoprostone as a cervical ripening agent in underdeveloped countries with poor socioeconomic condition. DOI: http://dx.doi.org/10.3126/njog.v3i2.10826 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 16-20